Aspek Moral Hukum Penerapan Prinsip Mengenali Pengguna Jasa Dalam Transaksi Perubahan Perseroan Terbatas Oleh Notaris Di Wilayah DKI Jakarta - Shahrandy Prakoso Hartono; Mohammad Ryan Bakry; Chandra Yusuf (Syntax Idea)
Moral law in the application of the principle of recognizing service users by notaries is the main principle in using notary authority in limited liability company change transactions, where steps and actions are implemented to ensure that notaries carry out their duties by complying with the quality of complying with the law, being independent, neutral, and adhering to ethics. notary profession and preventing money laundering crimes. This is in line with integrity, justice and moral principles that apply in law, both in the government environment and in the community that uses notary services. The position of the principle of recognizing service users for notaries based on legal morals is illustrated through two main aspects. First, the internal aspect which involves internal monitoring and sanctions mechanisms that ensure notaries comply with these principles through a supervision system within notary organizations and supervisory councils in the DKI Jakarta area. Second, external aspects through coordination with government agencies or policy makers to ensure notaries can implement the principle of recognizing service users, including through outreach activities and compliance audits in the DKI Jakarta area